Activatable semiconducting polymer pro-nanomodulators for deep-tissue sono-immunotherapy of orthotopic pancreatic cancer - Li, Jingchao (2023)
Immunotherapy has provided a promising modality for cancer treatment, while it often has the issues of limited response rates and potential off-target side effects in clinical practice. We herein report the construction of semiconducting polymer pro-nanomodulators (SPpMs) with ultrasound (US)-mediated activatable pharmacological actions for deep-tissue sono-immunotherapy of orthotopic pancreatic cancer. Such SPpMs consist of a sonodynamic semiconducting polymer backbone grafted with poly(ethylene glycol) chains linked with two immunomodulators (a programmed death-ligand 1 blocker and an indoleamine 2,3-dioxygenase inhibitor) via a singlet oxygen (1 O2 )-cleavable segment. In view of the excellent sonodynamic property of the semiconducting polymer core, SPpMs enable effective generation of 1 O2 under US treatment, even in a deep-tissue depth up to 12 cm. The generated 1 O2 not only ablates tumors via a sonodynamic effect and induces immunogenic cell death, but also destroys the 1 O2 -cleavable segments to allow in situ release of immunomodulators in tumors. This synergetic action results in boosted antitumor immune response via reversing two tumor immunosuppressive pathways. As such, SPpMs mediate deep-tissue sono-immunotherapy to completely eradicate orthotopic pancreatic cancer and effectively prevent tumor metastasis. Moreover, such an immune activation reduces the possibility of immune-related adverse events. This study thus provides a smart activatable nanoplatform for precise immunotherapy of deep-seated tumors.